PENGARUH PROFITABILITAS, LEVERAGE, PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN PROPERTIES DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2021-2024) - Arsifa Anggraeni; Yosevin Karnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to analyze and provide evidence of the effect of profitability, leverage, and company growth on firm value (Empirical Study of Property and Real Estate Companies Listed on the Indonesia Stock Exchange (IDX) for the period 2021-2024). The research population consists of all property and real estate companies listed on the Indonesia Stock Exchange for the period 2021-2024 using purposive sampling techniques. Data from 72 companies were obtained as samples, resulting in 288 observation data that were analyzed using multiple linear regression. The results of the study indicate that profitability, leverage, and company growth have a simultaneous significant effect on firm value. Furthermore, the results indicate that, partially, profitability does not affect firm value, leverage has a negative and significant effect, while company growth has a positive and significant effect. This research is expected to provide practical benefits for property and real estate companies, serving as a basis for consideration by companies and investors to increase firm value. Theoretically, this study supports signaling theory by indicating that aspects such as profitability and company growth can serve as signals for investors in assessing or deciding on a company's performance and prospects. Furthermore, this study also supportstrade-off theory by indicating that leverage can be a decision-making factor in achieving a balance between benefits and risks.